Impact of prefilter dilution on IgG removal in membrane‐based therapeutic plasma exchange. Issue 4 (5th December 2021) - Cabral, Paul; Kaplan, Andre A.; Phachu, Deep; Shah, Mamta; Attique, Hassan Bin; Elali, Ibrahim
Abstract: Introduction: Previous studies have demonstrated that a "one plasma volume exchange" would result in an estimated 63% decline in pretreatment IgG levels. We evaluated the use of prefilter dilution with normal saline as a method to prevent filter failure without decreasing the efficiency of IgG removal. Methods: Twenty‐one treatment sessions were analyzed and all received prefilter dilution with normal saline. Primary outcome was to determine whether prefilter dilution resulted in decreased treatment efficiency in removing the targeted IgG. Secondary outcome was filter failure in conjunction with the combined use of prefilter heparin and saline infusions. Results: All 21 treatments (100%) received prefilter dilution with saline solution and 19/21 (90.47%) also received prefilter heparin (bolus and/or hourly infusion). We demonstrated a 60%–70% decline in pretreatment IgG levels. Conclusion: Prefilter dilution during membrane‐based therapeutic plasma exchange based treatment did not result in a demonstrable decrease in efficiency of IgG removal while maintaining filter patency.